Self-medication in children and adolescents through parental influence: an integrative review (Research, Society and Development, 2022)
The use of drugs is a fundamental therapy and highly accepted by the population in the treatment of disorders of diffuse etiologies. Currently, self-medication in patients aged 0 to 15 years is mainly due to direct influence of their responsible/parents. Maniero et al., (2018) showed a 31.1% prevalence rate in child self-medication mediated by family members. Objectives: to highlight the aspects that characterize pediatric self-medication within the family, through the analysis of selected articles in virtual databases. Methodology: The present study consists of an integrative literature review, addressing the characteristics of pediatric self-medication associated with the role of parents in it. Results: 192 studies were found in 5 virtual databases: National Library of Medicine (NLM/MEDLINE), Scientific Electronic Library Online (SCIELO), Literatura Latino-Americana e do Caribe em Ciências (LILACS), Índice Bibliográfico Español en Ciencias de la Salud (IBECS) and Base de Dados em Enfermagem (BDENF). After implemen inclusion and exclusion criteria, a total of 15 articles were selected for discussion. Discussions: Self-medication rates of 29%, 17%, 15.7% and 20.2% were identified at 1 month, 1 year, 4 years and 15 years, respectively; the use of medication was reported as 64.7%, 52%, 35% and 30.9%, in the same time interval. Final Considerations: Self-medication is a common and worrying phenomenon. Furthermore, studies are needed to measure the rates of self-medication in children, to monitor the prevalence and prevent its increase.